ANALISIS PELATIHAN SHIP MANAGEMENT GUNA MENINGKATKAN KUALITAS KERJA AWAK KAPAL DI PT. PERTAMINA PERKAPALAN JAKARTA - Yogi Pangestu; Andy Wahyu Hermanto (Dinamika Bahari, 2018)
Pertamina Shipping Jakarta has training or training namely PMTC (PertaminaMarine Training Center) is a place to train employees to be able to improve the quality andquality of work, it has not gone well so it affects the quality of the crew's performance. Thepurpose of this study is to find out whether the ship management training program at PT.Pertamina Shipping Jakarta can reach the target optimally or not and to know the impact ofthe ship management training program on the quality of the work of the crew at PT.Pertamina Shipping Jakarta. This research uses descriptive qualitative method by describing in detail theimplementation of ship management training in order to improve the quality of work of thecrew at PT. Pertamina Shipping Jakarta. Data collection is done by interview, observation,literature study and documentation conducted by the author. The results of the study show that ship management training program at PT. PertaminaShipping Jakarta has not reached its target optimally because there are still seafarers whohave been on board the vessels that have not participated in the training, PT. PertaminaShipping Jakarta lacks staff training staff, the pre test system has not been held before beinggiven training. The impact of the ship management training program on the quality of thework of the crew as follows: ship management training on International Safety ManagementCode (ISM Code) makes the ship's crew understand more about international safetymanagement standards in the operation of ships as well as efforts to prevent or controlenvironmental pollution. carrying out Tank Cleaning, ship management training made thenewly joined crew members aware of the work system and procedures when they laterworked on the ship.